THE IMPACT OF GOOD CORPORATE GOVERNANCE ON FRAUD PREVENTION - Zhieren Adziqa As'ad; Erna Sulistyowati (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to test the impact of good corporate governance (GCG) on fraud prevention at Mining Company X. The sampling approach employed probability sampling with a basic random sampling procedure, yielding 94 respondents from a total of 1,451 permanent employees. This study employs a quantitative method, employing Partial Least Squares (PLS) analysis powered by SmartPLS 4.0 software. The results prove that GCG has a positive and significant effect on fraud prevention, with a p-value of 0.000 and a path coefficient of 0.736. The R² value of 0.542 suggests that GCG moderately contributes to explaining fraud prevention. These results highlight the crucial role of implementing GCG principles in establishing an effective anti-fraud system, particularly in mining companies that face high exposure to fraud risks.